A Pilot Web Based Positive Parenting Intervention to Help Bipolar Parents to Improve Perceived Parenting Skills and Child Outcomes. Issue 3 (May 2014) - Jones, Steven; Calam, Rachel; Sanders, Matthew; Diggle, Peter J.; Dempsey, Robert; Sadhnani, Vaneeta
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Children of bipolar parents are at elevated risk for psychiatric disorders including bipolar disorder. Helping bipolar parents to optimize parenting skills may improve their children's mental health outcomes. Clear evidence exists for benefits of behavioural parenting programmes, including those for depressed mothers. However, no studies have explored web-based self-directed parenting interventions for bipolar parents. Aims: The aim of this research was to conduct a pilot study of a web-based parenting intervention based on the Triple P-Positive Parenting Programme. Method: Thirty-nine self-diagnosed bipolar parents were randomly allocated to the web-based intervention or a waiting list control condition. Parents reported on their index child (entry criterion age 4–10 years old). Perceived parenting behaviour and child behaviour problems (internalizing and externalizing) were assessed at inception and 10 weeks later (at course completion). Fifteen participants (4 control group and 11 intervention group) did not provide follow-up data. Results: Levels of child behaviour problems (parent rated; Strengths and Difficulties Questionnaire) were above clinical thresholds at baseline, and problematic perceived parenting (self-rated; Parenting Scale) was at similar levels to those in previous studies of children with clinically significant emotional and behavioural problems. Parents in the intervention group reported improvements in child behaviour problems and problematic perceived parenting compared to controls. Conclusions: A web-based positive parenting intervention may have benefits for bipolar parents and their children. Initial results support improvement in child behaviour and perceived parenting. A more definitive study addressing the limitations of the current work is now called for.